Soda noteikšanas vispārīgie principi - Muste, Inta (Latvijas Universitāte, 2018)
Bakalaura darbs „Soda noteikšanas vispārīgie principi” ir noteikti Krimināllikuma 46.pantā. Soda noteikšanas vispārīgie principi, ir tie principi, kuri jāievēro, tiesai nosakot sodu un prokuroram piemērojot prokurora priekšrakstu par sodu. Tie ir pamata principi, lai tiktu piemērots taisnīgs sods. Soda piemērošana vienmēr būs aktuāla tēma, laikam ejot un mainoties izpratnei, sabiedrībai kļūstot humānākai, līdzcietīgākai, saprotošākai vienam pret otru, mainās arī izpratne, kas ir taisnīgs sods. Lai taisnīgu, samērīgu sodu varētu noteikt tiesa vai prokurors, piemērojot prokurora priekšrakstu par sodu, ir jāievēro soda noteikšanas vispārīgie principi. Bakalaura darba nozīmīgums izriet no Krimināllikuma 46.panta teorētiskā aspekta - laika gaitā, skatot no vēsturiskās attīstības līdz pat mūsdienām un piemērošanas, jeb praktiskās aspekta - analizējot tiesu praksi, kā arī salīdzinošā aspekta - salīdzinot Krimināllikuma 46.pantu ar ārvalstu regulējumiem. Lai gan soda noteikšanas vispārīgie principi ir diezgan sen institūts Latvijā, piemērojams, izprasts jau sen, taču vēl joprojām ir aktuāla problēma soda noteikšanas vispārīgo principu teorētiskajā izpratnē, gan arī praktiskajā piemērošanā. Bakalaura darba mērķa sasniegšanai autore izvirza šādus uzdevumus: 1)izpētīt juridiskās literatūras, avotos, normatīvajos aktos soda noteikšanas vispārīgo principu vēsturisko attīstību; 2)izpētīt juridiskās literatūrā, avotos, sniegtos viedokļus par soda noteikšanas vispārīgo principu jēdzienu un izpratni; 3)veikt tiesu prakses analīzi, izpēti soda noteikšanas vispārīgos principus un vērtēt to ietekmi uz soda veida noteikšanu un soda mēra piemērošanu; 4)veikt salīdzinājumu soda noteikšanas vispārīgiem principiem starp Latvijas un ārvalstu regulējumiem; 5)sniegt priekšlikumus soda noteikšanas vispārīgo principu institūta attīstībai un izpratnei.

Bachelor’s theses on “General principles for determination of punishment” are regulated in Criminal law article 46. General principles for determination of punishment are those principles that need to be respected, court determining punishment and prosecutors determining prosecutor's penal order. They are basic principles, to apply just punishment. Application of punishment will always be a topical subject, time passing by and change of understanding, society became more humane, more compassionate, more understanding for one and another, understanding of a just punishment, has also changed. So that courts and prosecutors could apply a just and proportional punishment, applying the prosecutor’s penal order, it is a must to respect general principles for determination of punishment. The importance of this bachelor’s thesis follows Criminal law article 46. theoretical aspect - during a period of time, looking from historical development till modern times and its application, or in a practical aspect – analysing court practice, as well as from comparative aspect – comparing Criminal law article 46. with foreign laws. Although general principles for determination of punishment is a pretty old institute in Latvia, applicable, understood long ago, but still is a topical subject in general principles for determination of punishment in the theoretical sense, as well as in practical application. In achieving the goal of this bachelor’s thesis, the author of the thesis, has set forth such tasks as, first task, find general principles for determination of punishment historical development in literature, sources and normative acts. Second task, find provided opinions on the concept and understanding of general principles for determination of punishment in literature and sources. Third task, carry out court practice analysis, search about general principles for determination of punishment and evaluate impact on determination of the type of punishment and the application of the sentence. Fourth task, make a comparison of the general principles for determination of punishment between Latvia’s and foreign country laws. Fifth task, make proposals about the development and understanding of general principles for determination and punishment.
General principles for determination of punishment
Keywords: Juridiskā zinātne; sods; soda noteikšana; principi; soda veids; soda mērs